2014
DOI: 10.1038/ajg.2014.95
|View full text |Cite
|
Sign up to set email alerts
|

Physician Assessment and Management of Complex Colon Polyps: A Multicenter Video-Based Survey Study

Abstract: In this large survey of GIs and surgeons, physician specialty was strongly associated with accurate polyp characterization and a recommendation for endoscopic resection of complex polyps. Surgeons were most likely to recommend surgical resection of complex nonmalignant colorectal polyps compared with specialists in complex polypectomy who were the least likely. Therefore, collaboration with specialists in complex polypectomy may be helpful in determining the appropriate management of complex colon polyps. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 23 publications
2
42
1
Order By: Relevance
“…In addition, a population-based study which reported a surgical resection rate of 21% for benign polyps ≥ 20 mm in size [17] highlighted that the diagnosing endoscopist was an important factor in the variation in surgical referral rates. This is consistent with the finding that the specialty of the endoscopist is strongly associated with the accuracy of polyp characterization and treatment recommendations [18]. We hypothesize that the same effect may account for the findings of our study, in that the robust quality assurance and accreditation process of the national BCSP equips certified endoscopists to comprehensively assess colorectal polyps and optimize treatment decisions accordingly.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a population-based study which reported a surgical resection rate of 21% for benign polyps ≥ 20 mm in size [17] highlighted that the diagnosing endoscopist was an important factor in the variation in surgical referral rates. This is consistent with the finding that the specialty of the endoscopist is strongly associated with the accuracy of polyp characterization and treatment recommendations [18]. We hypothesize that the same effect may account for the findings of our study, in that the robust quality assurance and accreditation process of the national BCSP equips certified endoscopists to comprehensively assess colorectal polyps and optimize treatment decisions accordingly.…”
Section: Discussionsupporting
confidence: 91%
“…Assessment of resectability correlates with the experience of the examiner. It has been shown that some polyps deemed not to be resectable by one endoscopist may be resected when referred to expert centres,276–281 so automatic referral of these patients to surgery does not seem to be justified. In these expert centres, around 10% of patients ultimately undergo surgery for different reasons 282…”
Section: The Standardsmentioning
confidence: 99%
“…Despite the evolution of advanced polypectomy techniques, such as endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD), the numbers of patients undergoing resectional surgery for significant, but benign, colorectal polyps has remained relatively static [15]. Population-level data suggest that the variation in referral rates for surgical resection is associated with individual endoscopists and their specialty [16], with surgeons more likely to recommend surgical resection as a treatment modality [17]. Thus, specialist 'tribalism' continues to dominate the management of SPECC lesions and may be alleviated by a multidisciplinary referral process which facilitates appropriate allocation of treatment based on clinical need.…”
Section: Multidisciplinary Team Inputmentioning
confidence: 99%